ДАВРИЙ НАШРЛАРДА ЖАНУБИЙ ОРОЛБЎЙИ ҚОРАҚАЛПОҚЛАРИНИНГ ИЖТИМОИЙ-ҲУҚУҚИЙ АҲВОЛИГА ОИД АЙРИМ МАЪЛУМОТЛАР (ХIХ АСРНИНГ СЎНГГИ ЧОРАГИ – ХХ АСР БОШЛАРИ) - Абдуллаева, А.А. (SCIENCE and SOCIETY, 2022)
This article reflects, analyzes articles and information related to the public and legal administration of the territory in official periodicals, which were widely distributed during the administration of the region by the Russian Empire and were considered the only propagandists of imperial policy in the South Aral Sea region, Turkestan. In particular, it is written about the situation in the Amu Darya department, types of taxes, the development of trade in cities, the activities of the Aral Flotilla, types of fish and trade, and even about the fact that fish were sent to Baku, Astrakhan and other cities.